A comparison of the electronics industry of India and Korea - Khan, Mohsin U.
A comparison is made between the electronic industries of India and South Korea, the latter having a target oriented approach. However it is suggested that India should concentrate on achieving support from components suppliers.
This paper is a comparative study of the electronics industry of India and South Korea. The study shows how Korea has developed over the last twenty years in the area of electronics because of its target-oriented policy towards export, whereas India could not develop its electronics industry due to overemphasis on indigenisation, with the result it could not catch up with advances abroad in electronics technology and ended up with a weak electronic component industry. The paper concludes with some suggestions to develop the Indian software industry. This is the area where India could compete with other developing countries. At this stage India should not get involved so much in developing computer hardware without the support of a strong competent industry.
Keywords: Electronics industry